Pengaruh Model Pembelajaran PBL Berbasis Computational Thingking terhadap Hasil Belajar Siswa pada Mata Pelajaran Bahasa Indonesia - Syahrani , Syahrani; Purwono, Agung (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2024)
PBL's computational thinking-based learning model is a learning model that emphasizes contextual problem solving using the principles of computational thinking in the problem-solving process. This study aims to determine the impact of the application of the computational thinking-based learning model of PBL on the learning outcomes of students in grade IV MIN 2 Mojokerto. This study is conducted to evaluate the effectiveness of the learning model in improving the understanding of the students in the problem-solving process. The study is a quantitative study using the One Group Pretest Postest method with samples taken from students of 4th grade A MIN 2 Mojokerto of a total of 27 students conducted on January 17, 2024. The data analysis used was the descriptive test, the paired sample T-test, and the N-Gain test. The average pretest score was 46.48, and the average posttest value was 76.03. As for the paired sample test, T-Test obtained a Sig. (2-tailed) score of 0.000 < 0.05, so H was rejected and H1 accepted. Moreover, the N-Gain score was 0.3 < 0.5393 < 0.7, so it could be concluded that the PBL learning model based on computational thinking had a moderate influence on student learning outcomes, which means that the application of the problem-based learning model (PBL) based on computational thinking had a significant, but not very strong, impact on improving student learning results.